Bleeding Scores for the Diagnosis of von Willebrand Disease - Bowman, Mackenzie L.; James, Paula D. (Seminars in Thrombosis and Hemostasis, 2017)
Obtaining a personal history of bleeding is a critical component to the diagnosis of von Willebrand disease (VWD). The collection of this information can be challenging for physicians, however, as the reporting and interpretation of bleeding symptoms is subjective. The need for more precise quantification of bleeding symptoms was recognized and the Vicenza Bleeding Questionnaire was developed in 2005. This questionnaire collects data regarding the presence and severity of bleeding symptoms and generates a bleeding score by summing the severity of all symptoms reported by a patient. Several subsequent bleeding assessment tools (BATs) have been developed based from this original questionnaire and there has been a surge in the use of BATs in various clinical settings for the diagnosis and evaluation of VWD. This review will discuss the evolution of BATs over the past decade, as well as their use and validation in various settings for the diagnosis and evaluation of VWD. Additionally, we will discuss the clinical utility of BATs, the limitations of these tools, and future directions.
Keywords: bleeding questionnaire; bleeding score; von Willebrand disease